ANAK SAH MENURUT KHI PERSPEKTIF MAQASID SYARIAH - Indah Rizqi Sofyan (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
The importance of a child's legitimate lineage status impacts the rights they receive, such as the right to maintenance, inheritance, custody, and identity recognition. Additionally, it affects the child's psychological development because children born out of wedlock or labeled as illegitimate are likely to be bullied and ostracized by their peers, which can hinder their psychological growth and lead to deterioration. This study aims to examine the provisions in the Compilation of Islamic Law (KHI) regarding the status of legitimate children, explore the legal foundations used, and analyze the practical implications of these provisions. The research employs a literature study method by collecting information from sources such as journals, books, documents, and manuscripts relevant to the research topic through the maqasid shariah theoretical approach. The findings indicate that KHI prioritizes the welfare of preserving lineage (hifdzu al-nashab) over the preservation of religion (hifdzu ad-din) to ensure children receive their rights, including maintenance, inheritance, custody, and identity recognition. However, there is a negative aspect, as this could lead to an increase in extramarital relationships since zina (fornication) is considered haram, and the existence of such laws might cause society to trivialize zina, leading to a rise in issues related to fornication.